The effect of exercise on thermo-tolerance in pregnant Holstein heifers - Johnson, Jessica (Kansas State University, 2016)
Dairy cows require a low-stress environment in order to efficiently produce milk, and thus stress management is a common focal point for both researchers and producers. A primary source of stress for dairy cattle is associated with the environment, particularly heat, and therefore a considerable amount of research has been done in an attempt to find ways of reducing heat stress. Most of the research, however, has focused on using heat abatement techniques to cool the cow, using evaporative cooling systems to reduce temperature in the environment thus also cooling the cow, and selective breeding to improve thermal tolerance. Whereas cow comfort has been improved, there are still negative responses to heat stress today including decreased milk production and altered milk composition. Cattle remove excess body heat primarily through evaporative and convective cooling in the respiratory system and exercise is likely to improve blood flow and efficiency of heat transfer within the lungs. Furthermore, exercise has been proven to improve performance in humans and horses. This study was designed to determine whether or not exercise improved fitness and heat tolerance, and to observe whether there were any resulting effects on milk production and parturition. Two experiments were carried out during the late summer/early fall of 2014 and summer of 2015. Each experiment utilized a different exercise regimen: experiment 1 used a combination of high-intensity intervals and endurance training, whereas experiment 2 involved an endurance regimen performed during the afternoon in early summer. Pregnant Holstein heifers (Experiment 1, n = 24; Experiment 2, n = 24) were exercised in an 8-panel motorized walker over a period of 8 wk that ended approximately 21 d prior to parturition. In experiment 1, fitness was improved in heifers that were exercised compared with their non-exercised counterparts based on their duration of exercise and speed of exercise at failure (P < 0.05). During a cool hour of the day after 6 wk of exercise, exercised heifers spent more time in body temperature zone 1 (< 39.0°C) compared with their non-exercised counterparts (P < 0.05). Exercised heifers also spent less time (P < 0.05) than non-exercised heifers in body temperature zone 3 (> 40.0°C) during the hottest hour of a hot day during the 6th week. No treatment effects (P > 0.10) were found for weekly milk components or milk production. In experiment 2, exercise resulted in greater milk protein and solids-not-fat (SNF) percentage (P < 0.05) compared with contemporaries that did not exercise; however, there was no difference in weekly milk production during the first 150 days (P > 0.10). Fat-corrected milk and energy-corrected milk were calculated and no difference was detected between treatments (P > 0.10). These results are the first to show that high-intensity intervals and endurance training exercise in pregnant dairy heifers can improve heat tolerance, increase production of milk protein and SNF, and perhaps increase animal comfort and well-being during hot weather.
Keywords: dairy cattle; heat toleranceexercise